hilD Is Required for the Active Internalization of Salmonella Newport into Cherry Tomatoes - Aurora Dolores Arista-Regalado; Jeannette Barba-León; Victor Humberto Bustamante; Mario Alberto Flores-Valdez; Jorge Gaona; Maira Juliana Fajardo-Guerrero (Journal of Food Protection, 2023)
Salmonella enterica is a foodborne pathogen that can be internalized into fresh produce. Most of the Salmonella virulence genes are clustered in regions denominated Salmonella Pathogenicity Islands (SPI). SPI-1 encodes a Type Three Secretion System (T3SS-1) and effector proteins that allow the internalization of Salmonella into animal cells. HilD is a transcriptional regulator that induces the expression of SPI-1 genes and other related virulence genes located outside of this island. Here, we assessed the role of hilD in the internalization of Salmonella Newport and Typhimurium into cherry tomatoes, by evaluating either an isolate from an avocado orchard, S. Newport-45 or the laboratory strain S. Typhimurium SL1344 and their isogenic mutants in hilD. The internalization of these bacteria was carried out by using a temperature gradient of 12°C. The transcription of hilD and invA was tested by qRT-PCR experiments. Our results show that S. Newport-45 hilD mutant viable cells obtained from the interior of the fruit were decreased (2.7-fold), compared with those observed for S. Typhimurium SL1344. Interestingly, at 3 days postinoculation, the cells recovered from S. Newport-45 hilD mutant were similar to those recovered from all the strains evaluated, suggesting that hilD is required only for the initial internalization of S. Newport.